The Effect Of Financial Literacy, Paylater Preference, And Cash Flow Management On The Cash Flow Resilience Of Generation Z Students In The E-Commerce Era - Louis Enrico; Thomas Christopher; Arion Sahputra Marasi Malau; Khana Saputri; Dwita Sakuntala (International Journal of Marketing & Human Resource Research, 2026)
The expansion of digital financial services, particularly the Paylater feature on e-commerce platforms, has increased transaction flexibility among Generation Z students while also heightening short-term liquidity risks. Prior studies have largely focused on financial literacy and fintech usage from a behavioral perspective, with limited attention given to cash flow resilience as a direct indicator of individual financial stability. This study aims to examine the effects of financial literacy, Paylater preference, and cash flow management on the cash flow resilience of Generation Z students in the e-commerce era. A quantitative explanatory design was employed involving 300 respondents selected through purposive sampling. Data were analyzed using multiple linear regression. The findings indicate that financial literacy and cash flow management have a positive and significant effect on cash flow resilience, while Paylater preference has a negative and significant effect. Cash flow management emerges as the most dominant variable, and the three predictors jointly explain 42.7% of the variance in students’ cash flow resilience. These results highlight that students’ financial stability is multidimensional, shaped by the interaction between cognitive capacity, digital consumption behavior, and financial management discipline. This study contributes to the digital financial behavior literature by positioning cash flow resilience as an indicator of sustainable financial stability in the digital economy context.